The Islamic Boarding School Education System in Improving the Life Skills of Students at the Darul Ihsan Islamic Boarding School - Munawaroh Nasution, Putri Ayu; Siregar, Alimuddin; Sundari, Dewi (Jurnal Ilmu Pendidikan Islam, 2024)
This study aims to analyze the education system at the Darul Ihsan Islamic boarding school in improving the life skills of students. The research method used is qualitative with a descriptive approach. Data collection techniques use observation, interviews, and documentation. Data analysis techniques through the stages: data condensation, data presentation, and drawing conclusions and verification. The results of the study indicate that the Darul Ihsan Islamic boarding school creates a modern education model, where teaching techniques, subject matter, and facilities and infrastructure are designed in accordance with contemporary educational principles. Efforts to improve the life skills of students, the management of the Islamic boarding school involves several strategic areas, including Madrasah Diniyah, routine religious studies, student organizations, curriculum, and facilities and infrastructure. This life skills development is an integral part of the entire education system at the Darul Ihsan Islamic Boarding School, which aims to equip students with balanced academic and practical skills.